Romance [compact disc] - Lang, Lang, 1982-; Liszt, Franz, 1811-1886; Bach, Johann Sebastian, 1685-1750; Chopin, Frédéric, 1810-1849; Tchaikovsky, Peter Ilich, 1840-1893; Chopin, Frédéric, 1810-1849; Zimmer, Hans; Bach, Johann Sebastian, 1685-1750; Tchaikovsky, Peter Ilich, 1840-1893; Chopin, Frédéric, 1810-1849; Schubert, Franz, 1797-1828; Chopin, Frédéric, 1810-1849; et al. (Sony Classical, 2017)
'Romance' showcases Lang Lang's innate yet sophisticated feeling for nuance and reflection. Carefully selected from his Sony Classical discography, the selections achieve a fulfilling programmatic unity through subtle contrasts in mood and style.